Deglacial environmental changes on Isla de los Estados (54.4°S), southeastern Tierra del Fuego - Unkel, Ingmar; Björck, Svante; Wohlfarth, Barbara (Quaternary science reviews, 2008)
The island of Isla de los Estados is situated at 54.5°S, 64°W, east of Argentinian Tierra del Fuego, and is located in a sensitive geographic position in relation to the zonal circulation between Antarctica and South America. Its terrestrial records of the last deglaciation, recording atmospheric conditions but within an oceanic setting, can help to clarify changes of regional circulation patterns, both atmospheric and marine. Here, we present geochemical analyses from 16-10kacalBP of a peat core from Lago Galvarne Bog at the northern coast of the island, and a lake sediment core from Laguna Cascada 3km further south. The data comprise TC, TN, loss on ignition analyses and continuous XRF scanning on both cores as well as age-depth modeling based on AMS-14C dating. Deglaciation and onset of peat formation in the coastal areas began before 16kacalBP followed by a rapid glacial retreat and the start of lacustrine sedimentation further inland. Data suggest initially windy conditions with permafrost succeeded by gradually warmer and wetter conditions until ca 14.5kacalBP. The warming trend slows down until ca 13.5kacalBP, followed by arid conditions culminating around 12.8kacalBP. Our data suggest fairly warm conditions and the establishment of denser peat and forest vegetation ca 10.6kacalBP, contemporaneous with the onset of the Antarctic thermal optimum. This indicates large-scale shifts in the placement of zonal flow and the Westerlies at the beginning of the Holocene.
Online veröffentlicht: 1. Juli 2008
Gesehen am 19.02.2025